ANALISIS PENGARUH PROMOSI , BRAND AWARENESS, CITRA DESTINASI TERHADAP KEPUASAN BERKUNJUNG WISATAWAN DI KOTA TANGERANG SELATAN - Verry cyasmoro (LPPM Universitas Asa Indonesia, 2019)
This research aims to know the influence of Promotion , brand Awarenees , destination image variable on tourist satisfaction against Situ Gintung Park and BSD Ocean Park, South Tangerang City, Banten. This research uses descriptive and quantitative approach. The collection of data obtained through a questionnaire which distributed to 100 respondents. The sampling technique of this research using purposive sampling and the respondent is domestic tourist, at least two visits. The results showed that: destination image variable significantly influence tourist satisfaction, the destination image variable significantly influence tourist Statisfaction variable, and tourist satisfaction variable significantly influence tourist Brand awareness. Based on this findings, the government and the tourism’s entrepreneur have to keep the image of South Tangerang city up and increase the tourist’s visit intention by promoting all types of tour attraction, and optimizing the variety of tour attraction by creating tour promotion.